Audience : marketing in the age of subscribers, fans & followers - Rohrs, Jeffrey K. (Hoboken, New Jersey : John Wiley & Sons, 2014)
Explains how marketers can build and keep an online audience through the use of hybrid marketing strategies that rely on combinations of old-fashioned mass media with newer email, mobile, and social media platforms.
Audiences as assets: think like the boss -- The audience imperative: our hybrid source of business energy -- Your proprietary audiences: seekers, amplifiers & joiners -- The VIP joiners: subscribers, fans & followers -- Beyond Don Draper: pain, owned & earned media -- Increase what matters: size, engagement & value -- A larger font: our long-term responsibilities -- Website: marketing's magnetic center -- Email: the bedrock audience -- Facebook: making it personal -- Twitter: real-time characters -- Blogs: a website by another name -- Mobile apps: audiences on the go -- LinkedIn: the professional audience -- YouTube: internet built the video star -- Google+: the great unknown -- Pinterest: a collection of beautiful followers -- SMS: cutting through the cutter -- Instagram: moving pictures -- Podcasts: listen carefully -- Other audience channels: more? You want more?!? -- Map & align: strategy and team -- Built & engage: audiences on demand -- Serve, honor, deliver, surprise & delight: the red velvet touch -- Test & evolve: what marketers can learn from 5,000 years of football.
Includes bibliographical references (pages 249-272) and index.
Keywords: Internet marketing; Social media